Supplementation of hairy eggplant (Solanum ferox) and bitter ginger (Zingiber zerumbet) extracts as phytobiotic agents on whiteleg shrimp (Litopenaeus vannamei) (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: This study aimed to evaluate the combination of hairy eggplant (Solanum ferox) and bitter ginger (Zingiber zerumbet) on the production performance and hematological parameters of whiteleg shrimp (Litopenaeus vannamei). Materials and Methods: Four treatments were formulated in the test feed, where P1 (control + commercial vitamin C); P2 (120 ml/l combination of S. ferox and Z. zerumbet); P3 (100 ml/l); and P4 (80 ml/l) 6,000 post-larvae shrimp with an average initial weight of 0.2 gm were randomly stocked in four groups, with three replications per treatment, and 500 were stocked in each pond with a total of 12 pounds. Results: Based on the results, there were significant differences in production performance (survival, absolute weight growth, specific growth rate, and feed conversion ratio). Biologically, the best performance was found in the P3 treatment (100 ml/l). In this treatment, the total number of hemocytes and the number of hyaline hemocytes were much higher, and this was not the case in the control treatment (P1), where the number of semi-granular and granular cells was significantly higher than the treatment group (p < 0.05). Conclusions: This study confirmed that supplementation of 100 ml/l of S. ferox and Z. zerumbet could improve the production performance and hemato-immunological parameters of whiteleg shrimp, with functional potential to be developed in phytobiotic-based commercial diets for shrimp. J. Adv. Vet. Anim. Res., 9(1): 78–86, March 2022http://doi.org/10.5455/javar.2022.i571